THE EFFECTIVENESS OF TASK-BASED TEACHING IN IMPROVING LANGUAGE PROFICIENCY AMONG SECOND LANGUAGE LEARNERS - Imtiaz Ali; Aasima Bibi; Kausar Ali; Uzma Aman; Shadab Kabir (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Task-Based Language Teaching (TBLT) works to improve students’ ability to communicate in a second language. TBLT focuses on authentic communication and cultural relevance through the utilization of relevant exercises for language acquisition. This research examines the effects of TBLT on the proficiency, communication skills, and task authenticity of L2 students in comparison to more traditional approaches. The review is based on the work of scholars including Prabhu, Nunan, Long, and Krashen, who created foundational ideas such as task authenticity, learner-centeredness, and cooperation. Multiple studies are analyzed to determine how TBLT affects one’s linguistic competence. Through metaphors, anaphors, and symbolism, TBLT is presented to students as a symphony of language, a garden where language flourishes, and a compass that leads to fluency. According to the results, TBLT benefits language learners by encouraging participation, independence, and cross-cultural awareness. Teachers should design authentic activities, promote interactive classrooms, encourage students to offer and receive feedback and rethink how language is evaluated. Ultimately, TBLT emerges as a transformative strategy that improves language learners’ skills, self-assurance, and cross-cultural perspectives, influencing new, more fruitful paradigms in language instruction.